Pengaruh Jalur Pelaporan dan Tingkat Religiusitas terhadap Niat Seseorang Melakukan Whistleblowing - Caesar Marga Putri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2016)
The purpose of this research is to examine empirically the effect of reporting channel (anonymous and non anonymous) in the structural model and the effect of religiousity level on individual intention to report wrongdoing act. The design used in this experiment is 2x2 between subjects, with graduate level student as participant. The result shows that anonymous reporting channel in the structural model is more effective than non-anonymous reporting channel. The result that religiousity level will affect the individual intention to report wrongdoing is unpredicted. This research shows that religiousity level is not effect individual intention to report wrongdoing.